(untitled) (Res Medica, 2013)
TABLE OF CONTENTS EDITORIAL SYLLABUS FOR 222nd SESSION CANCER RESEARCH: ITS HISTORY AND PROSPECTS: Professor Alexander Haddow, M.D., D.Sc.,F.R.S. THE SOCIETY’S LIBRARY: J. J. C. Cormack BIOLOGICAL RESERVES: Sir James Learmonth, K.C.V.O., C.B.E., F.R.S.Ed., F.R.C.S.Ed. and Eng., M.D. THE CAUSATION AND SPREAD OF EPIDEMIC INFLUENZA: William Ian Shedden, B.Sc.(Hons.) SOME ASPECTS OF POLIOMYELITIS: Allan Milne,M.B., Ch.B. BOOK REVIEW OPERA OCCULTA: Henry C. Drysdale